THE INFLUENCE OF RUSSIAN SYMBOLISTS’ LITERATURE STUDIES ON V. M. ZHIRMUNSKY’S UNDERSTANDING OF POETICS AS AN ACADEMIC DISCIPLINE (Филологический класс, 2019)
The theoretical heritage of Russian symbolists affected not only the establishing of formalism in Russia, but the forming of a view of poetics as an academic discipline in the works of V. M. Zhirmunskiy. If the “Those Who Overcame Symbolism” can be seen as the manifesto of acmeism, then the “Goals of Poetics” is an equally brilliant manifesto of the new literature studies of the 1910s–1920s. Zhirmunskiy’s initial thesis is very poignant. The article deals with different editions of V. M. Zhirmunskiy’s “Goals of Poetics”, which mirrored his attitude towards the philological heritage of Russian symbolism. The initial edition of 1921 and the final edition have substantial differences. The article also deals with Zhirmunskiy’s prologue to the book “Issues of the Theory of Literature” (1928), which helps shed new light on his evaluation of Russian symbolists in the final edition of the “Goals of Poetics”. For example, in the late 1920s Zhirmunskiy views Bryusov’s role in establishing poetics as an academic discipline in a slightly different way, compared to the initial text of the “Goals of Poetics”. Thus, the purely theoretical aspect of comprehending the symbolists’ heritage intertwines with the literary-aesthetic fight of those years. The understanding of poetics as an academic discipline by Zhirmunskiy, the formalists and in the literature studies of the 1910s–1920s in general goes back to the theoretical heritage of Russian symbolism.